Moisture Sources for the Precipitation of Tropical-like Cyclones in the Mediterranean Sea: A Case of Study - Patricia Coll-Hidalgo; Albenis Pérez-Alarcón; Raquel Nieto (Atmosphere, 2022)
Tropical-like cyclones (TLCs) are hybrid low-pressure systems formed over the Mediterranean Sea, showing the characteristics of tropical and extratropical cyclones. The literature review revealed that several studies have focused on determining the physical mechanisms that favour their formation; however, their rainfall has received little attention. In this study, we attempted to identify the origin of the precipitation produced by TLCs through a Lagrangian approach based on the analysis of moisture sources for the TLC Qendresa from 6 to 9 November 2014. For the Lagrangian analysis, we used the trajectories of air parcels from the global outputs of the FLEXPART model fed by the ERA-5 reanalysis provided by the European Centre for Medium-Range Weather Forecast and backtracked those parcels that precipitated within the outer radius of the storm up to 10 days. Our results showed that the moisture mainly came from the western Mediterranean Sea, Northern Africa, the central Mediterranean Sea, Western Europe, the eastern North Atlantic, and the eastern Mediterranean Sea with contributions of 35.09%, 27.6%, 18.62%, 10.40%, 6.79%, and 1.5%, respectively. The overall large-scale conditions for the genesis of Qendresa agreed with previous climatological studies. Therefore, our findings contribute to the understanding of precipitation associated with TLCs. Future studies will focus on a climatological analysis of the origin of rainfall produced by these hybrid cyclones.